2018
DOI: 10.3233/xst-17350
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CT Hounsfield Units for 3D acquisition trajectories on a dedicated breast CT system

Abstract: Hounsfield Units (HU) are used clinically in differentiating tissue types in a reconstructed CT image, and therefore the HU accuracy of a system is important, especially when using multiple sources, novel detector and non-traditional trajectories. Dedicated clinical breast CT (BCT) systems therefore should be similarly evaluated. In this study, uniform cylindrical phantoms filled with various uniform density fluids were used to characterize differences in HU values between simple circular and complex 3D (saddl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Furthermore, an MRI system is superior because of its ability to sensitively identify differences in internal information. Since the X-ray transmittance is reflected in an image in CT (Shah et al 2018), the change in the pixel value of a soft tissue image is small. However, in MRI, the distinction in a composition is evident because characteristic values such as proton density and relaxation time (T1 and T2) are reflected in the pixel value.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an MRI system is superior because of its ability to sensitively identify differences in internal information. Since the X-ray transmittance is reflected in an image in CT (Shah et al 2018), the change in the pixel value of a soft tissue image is small. However, in MRI, the distinction in a composition is evident because characteristic values such as proton density and relaxation time (T1 and T2) are reflected in the pixel value.…”
Section: Discussionmentioning
confidence: 99%
“…Dedicated breast computed tomography (DBCT) is a recently used and fastest-growing imaging technique that allows for true isotropic and provides three-dimensional (3D) information which can be reconstructed or rebuilt into several imaging planes. Although DBCT is comparable to breast magnetic resonance imaging (MRI), the process involved can be carried out without breast compression, and is not limited by breast implants or the density of the breast [ 41 , 42 , 43 ]. The radiation dose in this type of imaging technique is similar to that of a conventional two-view mammogram [ 42 ].…”
Section: Types Of Biomedical Imagingmentioning
confidence: 99%
“…The invention, improvement, and development of DBCT with dedicated scanners with novel technology has been documented in the literature by Sarno et al [ 45 ]. Studies further reported the development of low radiation dose scanners with improved spatial resolution and rapid image acquisition times, which is aimed at addressing the issue of imaging dense breasts and painful breast compression [ 41 , 42 , 43 ].…”
Section: Types Of Biomedical Imagingmentioning
confidence: 99%
See 1 more Smart Citation